Supplementation with Chlorella vulgaris, Chlorella protothecoides, and Schizochytrium sp. increases propionate-producing bacteria in in vitro human gut fermentation - Jin, Jong Beom; Cha, Jin Wook; Shin, Il-Shik; Jeon, Jin Young; Cha, Kwang Hyun; Pan, Cheol-Ho (John Wiley & Sons Inc., 2020)
BACKGROUND Gut microbiota are major contributors to host metabolism and are considered as potential targets of novel therapeutics. Microalgae have a strong potential for use as prebiotics because they are a rich source of proteins, fatty acids, fiber, and minerals for nutritional supplementation in humans. Nevertheless, there has been insufficient research into the effect of microalgae on gut microbiota. To investigate the effects of three edible microalgae (Chlorella vulgaris, Chlorella protothecoides, and Schizochytrium sp.) on gut microbiota, simulated digestion and colonic fermentation were examined. RESULTS Following in vitro digestion, the microalgae displayed different levels of bioaccessibility and the nutrient analysis revealed that unabsorbed nutrients during the digestion process could be used for colonic fermentation. Following colonic fermentation, the control, inulin, and microalgae groups displayed different metabolite tendencies when investigated with nuclear magnetic resonance (NMR) spectroscopic analysis. In particular, microalgae supplementation increased the proportion of propionate in the colonic culture (control: 19.14%, Inulin: 18.38%, C. vulgaris: 25.80%, C. protothecoides: 25.46%, and Schizochytrium sp.: 25.56%). Microbial profiling analysis using 16S rRNA gene sequencing also disclosed that the relative abundance of Bacteroides (control: 1.91%, inulin: 2.61%, C. vulgaris: 14.77%, C. protothecoides: 11.17%, and Schizochytrium sp.: 5.51%) and Dialister (control: 0.08%, inulin: 2.06%, C. vulgaris: 6.79%, C. protothecoides: 4.45%, and Schizochytrium sp.: 4.48%), involved in propionate metabolism increased more than in the inulin group. CONCLUSION Our findings suggest the potential use of microalgae as a functional food to increase propionate generation because propionate has been reported to be effective in weight loss and the inhibition of pathogen infection. (c) 2020 Society of Chemical Industry